Different colonization patterns of Aspergillus terreus in patients with cystic fibrosis. (9th August 2013) - Rougeron, A.; Giraud, S.; Razafimandimby, B.; Meis, J. F.; Bouchara, J.‐P.; Klaassen, C. H. W.; Roilides, E.
Abstract Aspergillus terreus is a common soil saprophyte. After Aspergillus fumigatus and Scedosporium apiospermum it ranks third amongst the filamentous fungi colonizing the airways of patients with cystic fibrosis. In this context, the clinical presentation of A. terreus infection mainly corresponds to allergic broncho‐pulmonary aspergillosis. In the work presented here, we studied colonization patterns of A. terreus in CF patients by genotyping using nine short tandem repeat markers. A total of 115 clinical isolates from respiratory secretions collected from five French CF patients were studied. The number of isolates varied from 15 to 39 per patient, and the duration of the follow‐up period ranged from 2 months to 7.5 years. Seventeen genotypes were identified, corresponding to three distinct colonization patterns. The first colonization pattern consisted of a chronic colonization by one dominant genotype associated with few other genotypes found only incidentally. The second colonization pattern consisted of a prolonged colonization by two distinct genotypes detected simultaneously. The last pattern was characterized by multiple different genotypes that were present only transiently. These results demonstrate the importance of genotyping clinical isolates before making conclusions about chronic colonization of the airways in CF patients in the case of repeated isolation of the fungus.